Competência internacional no Código de Processo Civil e princípios, à luz da jurisprudência do STF e STJ - Guerra, Marcel Vitor de Magalhães e (2010)
This paper analyzes the evolution of the methodology for applying the rules of international jurisdiction, Articles 88 and 89 of the CPC. The study analyzes the effects of the changing paradigm of law, with the increase of these possibles influences of the common law system in the national system, characterized by being hard. At the current stage of evolution, represented by a process of aligning systems and assessment of fundamental rights, has set itself an adaptation of traditional formal institutions, from principles aimed at justice, not admitting more restrictive interpretations of legal devices to limit their applications custom. So the magistrate shall be responsible for relaxation of rules on jurisdiction, promoting repair and adjustment of positive cases for the exercise of jurisdiction, where compliance represents a mechanical failure principles members of the legal system that are shaping the international court.